Radiation Dose In Non Conventional Contrast Radiography Examination - Darmini Darmini; J. Dahjono J. Dahjono; Asri Indah Aryani (Poltekkes Kemenkes Semarang, 2014)
This study aims to determine the radiation dose to the acceptance of conventional non- contrast radiographs and the dose received by the patient on a non contrast radiographs compared Perka BAPETEN According Reference No 8 of 2011.Quantitative research approach was applied in this research for the measurement of radiation using TLD chips. Furthermore, measurement results are sent to Batan. We analize the data by calculating the average radiation dose received at each examination on the TLD reader, and then compared them with the reference dose by Bapetten. Results indicate acceptance of the radiation dose on conventional radiographs thoracic lowest dose 0.262 mGy and the highest 0.41 mGy. Abdominal were 0.924 mGy and 1,913 mGy, AP lumbo sacral spine were 1.504 mGy and 1.965 mGy, and the lateral lumbo sacral were 2.522 mGy and 3.231 mGy. Comparation between the data and the Perka BAPETEN: the value of ESD on thoracic radiographs was 0.41 mGy (exceeding 0.4 mGy), abdominal radiographs was 1,913 mGy (less than 10 mGy) , lumbo sacral spine AP was 1,965 mGy, and lumbo sacral spine radiographs laterally was 3.231 mGy (less than 30 mGy).